TEACHING “PROPERTIES OF METALS” TO TECHNOLOGICAL EDUCATION STUDENTS USING MODERN INNOVATIVE PEDAGOGICAL TECHNOLOGIES (Scientific journal of the Fergana State University, 2026)
This article explores the use of modern innovative pedagogical technologies in teaching the topic “Properties of Metals” to students majoring in technological education and highlights their role in the learning process. It discusses the advantages of interactive, information-communication, problem-based, modular, project-based, and competency-oriented teaching technologies. The study also analyzes the effectiveness of using digital learning tools, laboratory experiments, and the integration of theoretical and practical knowledge. It is shown that these technologies help develop students’ independent thinking, scientific analysis, and creative approaches, increasing learning efficiency by 20–30%.